GmFT3a fine-tunes flowering time and improves adaptation of soybean to higher latitudes - Yuan, Shan; Wang, Yining; Wang, Junya; Zhang, Chunlei; Zhang, Lixin; Jiang, Bingjun; Wu, Tingting; Chen, Li; Xu, Xin; Cai, Yupeng; Sun, Shi; Chen, Fulu; et al. (Frontiers in Plant Science, 2022)
Onset of flowering of plants is precisely controlled by extensive environmental factors and internal molecular networks, in which FLOWERING LOCUS T (FT) is a key flowering integrator. In soybean, a typical short-day plant, 11 FT homologues are found in its genome, of which several homologues are functionally diversified in flowering pathways and the others including GmFT3a are yet unknown. In the current study, we characterized GmFT3a, which is located on the same chromosome as the flowering promoters GmFT2a and GmFT5a. Overexpression of GmFT3a significantly promoted flowering of Arabidopsis under the inductive long-day (LD) photoperiod. GmFT3a over-expressed soybean also flowered earlier than the control under LD, but they were not significantly different under inductive short-day (SD) conditions, indicating that GmFT3a acts as a flowering promoter in the non-inductive photoperiod in soybean. Compared with other GmFT homologues, GmFT3a exhibited a slighter effect in flowering promotion than GmFT2a, GmFT5a and GmFT2b under LD conditions. GmFT3a promoted flowering by regulating the expression of downstream flowering-related genes and also affected the expression of other GmFTs. According to the re-sequencing data, the regional distributions of two major haplotypes in 176 soybean varieties were analyzed. The varieties with GmFT3a-Hap2 haplotype matured relatively early, and relative higher expression of GmFT3a was detected in early maturing varieties, implying that Hap2 variation may contribute to the adaptation of soybean to higher latitude regions by increasing expression level of genes in metabolism and signaling pathways. The early flowering germplasm generated by overexpression of GmFT3a has potential to be planted at higher latitudes where non-inductive long day is dominant in the growing season, and GmFT3a can be used to fine-tune soybean flowering and maturity time and improve the geographical adaptation.